2011
DOI: 10.1002/alr.20023
|View full text |Cite
|
Sign up to set email alerts
|

High patient satisfaction after secondary rhinoplasty in cleft lip patients

Abstract: Patient satisfaction after secondary rhinoplasty in cleft lip patients is high and comparable to that of non-cleft lip rhinoplasty patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…One study found patients' ratings of their own appearance to be lower than ratings provided by professionals (Sinko et al, 2005). In contrast, patients gave more positive ratings of their own appearance when compared to professionals' ratings in three cases (Hens et al, 2011;Gkantidis et al, 2013;Byrne et al, 2014). In an analysis of specific facial features, Meyer-Marcotty and Stellzig-Eisenhauer gave higher ratings of appearance than those provided by laypersons (Chetpakdeechit et al, 2011;Eichenberger et al, 2014;Ferrari Júnior et al, 2015).…”
Section: Perceptions Of Appearance Among Professionals and Laypersonsmentioning
confidence: 99%
“…One study found patients' ratings of their own appearance to be lower than ratings provided by professionals (Sinko et al, 2005). In contrast, patients gave more positive ratings of their own appearance when compared to professionals' ratings in three cases (Hens et al, 2011;Gkantidis et al, 2013;Byrne et al, 2014). In an analysis of specific facial features, Meyer-Marcotty and Stellzig-Eisenhauer gave higher ratings of appearance than those provided by laypersons (Chetpakdeechit et al, 2011;Eichenberger et al, 2014;Ferrari Júnior et al, 2015).…”
Section: Perceptions Of Appearance Among Professionals and Laypersonsmentioning
confidence: 99%
“…Patients with body dysmorphic disorder (BDD) benefited less from rhinoplasty depending on the severity of BDD symptoms (11) . Hens et al (12) found that the postoperative satisfaction of cleft lip and non-cleft lip patients after secondary rhinoplasty was comparable.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies revealed mixed results, demonstrating that patients with clefts stated that their noses were either better or worse after skeletofacial surgical management than those with dentofacial deformities 8,15 . We hypothesized that as patients with clefts have received longitudinal multidisciplinary support since their infancy, they would have incorporated coping skills that helped them judge the surgical-induced nasal changes along with the presence of nasal deformities in a relatively positive perspective than their peers with dentofacial deformities 2,31,[42][43][44] .…”
Section: Discussionmentioning
confidence: 99%